P.118 Curriculum mapping can facilitate transition to Competence by Design. (November 2021) - Curtis, C; Mineyko, A
Abstract : Background: Curriculum maps outline the content of an educational program identifying links between targeted outcomes, educational opportunities, and assessments. The transition to Competence by Design (CBD) in Canadian specialty residency programs requires thoughtful reorganization of educational programming. A curriculum map may assist with understanding the existing curriculum and thereby facilitate planning for CBD. Methods: A map of the pediatric neurology residency curriculum at the University of Calgary was constructed by linking objectives with related learning activities and assessments. Qualitative line-by-line analysis was then conducted to identify gaps in the existing curriculum. The map was used as a framework to plot CBD outcomes and curricular structure as these were established. Results: Generating the traditional curriculum map was time-consuming, requiring 48 hours. Careful review identified several objectives that did not link to formal learning activities or assessments. Many such gaps were recognized to link to non-clinical activities. Using the scaffold of the traditional curriculum reduced the time required for mapping the planned CBD curriculum to 4 hours. Conclusions: The creation of a curriculum map prior to transition to CBD improved understanding of the existing curriculum and will facilitate transition to CBD. Ongoing evaluation of the fit of our predicted CBD map will support effective implementation.